Impact of Stone Size, Location, and Stone Composition on the Efficacy of Extracorporeal Shock Wave Lithotripsy for Residual Stone after Percutaneous Nephrolithotomy - Sawal, Zuhri; Soebadi, Doddy M (Folia Medica Indonesiana, 2020)
This study aimed to determine the impact of stone size, location and stone composition the efficacy of extracorporeal shock wave lithotripsy (ESWL) in the management of residual stone after percutaneous nephrolithotomy (PCNL). The design of this study was a retrospective that conducted between January 2012 until December 2016. The population in this study were all patients with residual stones post PCNL. Exclusion criteria were patients with multiple stones and patients with a history of previous treatment for residual stones such as nephroscopy, flexible ureterorenoscopy, ESWL or medical therapy). The variables studied in this study were stone size, stone location, and stone composition. Before ESWL was carried out, all patients underwent Kidney Ureter Bladder (KUB). After ESWL, all patients underwent ultrasonography (USG) and KUB to determine the stone clearance status. The sample of this study was 125 patients. The overall stone-free rate (SFR) of ESWL in managing post-PCNL residual stones is 72%. SFR based on stone size variable are 73.7% and 71.3% respectively for stones with a size = 5 mm and >5 mm (p = 0.78). SFR based on stone location variable was 67.1%, 75.8%, and 81.8% respectively for the residual stone located at the upper pole, middle pole and lower pole. There are no significant differences in the entire variable. This study concludes that ESWL can be used as effective additional management to treat post-PCNL residual stones with satisfactory SFR.